PROSPEK PENGEMBANGAN KELOR GUNA MENDUKUNG KETAHANAN PANGAN DI NUSA TENGGARA TIMUR - Kaleka, Marten Umbu; Puspita, Victoria Ayu; Ngaku, Maria Alfonsa (Agros Journal of Agriculture Science, 2023)
Moringa plants are excellent because they have high nutritional content, and economic value and are resistant to drought. This study aims to map potential opportunities and directions for developing moringa product businesses to support food security. The method used is a literature study method by collecting material from previous research. The results of the study show that moringa business opportunities in East Nusa Tenggara Province are very wide open for anyone. The number of moringa companies in this area is relatively small. Developing the moringa business to support food security by establishing policy direction, namely encouraging people to utilize the potential of dry land and increasing training and assistance in diversifying processed moringa products such as nuggets, noodles, pudding, cakes, tea, and moringa sticks into superior products in overcoming the problem of stunting and improving community income. Based on the results of the study, it can be concluded that developing Moringa into a superior product can create high added value, thereby providing large profits for managers and creating large employment opportunities for the community.. Key-words: Development, Food security, Moringa INTISARITanaman kelor menjadi primadona karena memiliki kandungan gizi yang tinggi, bernilai ekonomis, dan tahan terhadap kekeringan. Hampir semua bagian dari tanaman kelor dapat  bermanfaat untuk kehidupan manusia. Kajian ini bertujuan untuk memetakan peluang potensi serta arah pengebangan usaha produk kelor dalam mendukung ketahanan pangan. Metode yang digunakan adalah metode studi pustaka dengan mengumpulkan bahan hasil penelitian sebelumnya. Hasil kajian menunjukkan bahwa peluang usaha kelor di Provinsi Nusa Tenggara Timur sangat terbuka luas bagi siapapun. Jumlah perusahaan kelor di wilayah ini tergolong sedikit. Pengembangan usaha kelor dalam mendukung ketahanan pangan dengan menetapkan arah kebijakan yakni mendorong masyarakat memanfaatkan potensi lahan kering dan meningkatkan pelatihan dan pendampingan dalam  memversifikasi produk olahan kelor seperti nugget, mie, pudding, kue, teh, dan stik kelor menjadi produk unggulan dalam mengatasi persoalan stunting serta meningkatkan pendapatan masyarakat. Berdasarkan hasil kajian dapat disimpulkan bahwa pengembangan kelor menjadi produk unggulan dapat mencipatkan nilai tambah yang tinggi sehingga memberikan keuntungan yang besar bagi pengelolah serta menciptakan lapangan pekerjaan yang luas bagi masyarakat.  Kata kunci: Kelor, Ketahanan pangan, Pengembangan